In vitro propagation of Pyrus communis cv. Bartlett - PADDER, M A; MIR, M A; BHATT, K M; RATHER, Z A; HUSSAIN, G (The Indian Journal of Agricultural Sciences, 2012)
Shoot tip explants derived from forced and unforced explants were subjected to different sterilization regimes. Satisfactory culture asepsis (61.60%) and survival (45.00%) was obtained with 0.1% mercuric chloride when forced explants were used. MS medium supplemented with BAP+IBA (1.5+0.01mg/l) resulted in maximum explant establishment (46.66%). Maximum proliferating cultures (52.66%) and shoot number/explant (8.73) was recorded in MS medium supplemented with BAP+IBA (2.00+0.01mg/l). Microcuttings (10-15mm) from the proliferated cultures were inoculated in two media supplemented with different IBA concentrations for rooting. MS medium fortified with IBA (1.0 mg/l) resulted in maximum rooting (46.66%), root number/shoot (4.26) and root length (36.50 mm).